Being Sexual: Human Sexuality Revisited: Part Two of a Two-part Paper* (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
This second part of a two-part paper seeks to develop an existentially-informed approach to human sexuality that was initially presented in an earlier paper by the author (Spinelli, 1996) and which was re-viewed in Part One (Spinelli, 2013). Part One focused on an existential response to three key assumptions regarding human sexuality that have dominated contemporary sexological thought: namely, the links between sexuality and biology; notions of normality and abnormality; and the link between sexuality and personality or identity. This second part addresses the key existential assumption that 'existence precedes essence' and considers its implications for an existential approach to human sexuality. In particular, it addresses questions of otherness and gender.
Keywords: Essentialism; existence precedes essence; queer theory; sexual fluidity; dynamical systems theory; otherness; gender